The Impact of Atmospheric Correction on Brazilian Earth Tide Models - Arana, Daniel [UNESP]; Camargo, Paulo de Oliveira [UNESP]; Molina, Eder Cassola; Blitzkow, Denizar; de Matos, Ana Cristina Oliveira Cancoro; Boy, Jean Paul (Springer Nature, 2020)
Terrestrial gravity stations have been in operation for several years throughout Brazil. Minimizing geophysical effects on gravimetric observations is a major challenge in the generation of solid Earth tide models. The objective of this work was to conduct an analysis of barometric information and the impact of four barometric correction methodologies on gravimetric data for two stations located in the state of São Paulo: Presidente Prudente and Cananeia. The proposed approach involves three steps: (1) the processing of gravimetric data in order to obtain preliminary Earth tide models, (2) the application of four methodologies for atmospheric loading correction, and (3) the analysis of the impact on each wave constituent. The results show that the observed Earth tide models have a standard deviation (SD) of 0.001 and 0.01° for gravimetric factors and phases, respectively. The impact on the application of different methodologies for minimizing the air mass overload was less than 1.5 nm/s2 for the observation residuals. In addition, for both stations, the residuals in Earth tide constituents showed greater sensitivity to different atmospheric corrections for P1 and S2, which is related to the higher intensity of diurnal and semidiurnal solar constituents.
Keywords: atmospheric loading; barometric admittance; gPhone; Gravity